Engage, understand, listen and act: evaluation of Community Panels to privilege First Nations voices in pandemic planning and response in Australia - Adrian Miller; Sandra Campbell; Kristy Crooks; Kylie Taylor; Charlee Law (BMJ Global Health, 2022)
Introduction First Nations Peoples of Australia have not been included in the development nor prioritised in pre-2009 pandemic plans despite being a priority population in Australian health policy. Marginalised groups experience amplified barriers and systemic disadvantage in emergencies, however, their voices have not been heard in past pandemic responses. Through effective engagement with disadvantaged and oppressed groups, health authorities can gain a deeper understanding of how to design and implement pandemic control strategies. There have been limited studies with First Nations Peoples that has focused on pandemic planning and response strategies. Deliberative inclusive approaches such as citizens juries have been a way to uncover public perceptions.Methods Qualitative thematic research methods were used to conduct the study. We convened five First Nations Community Panels in three locations in Australia between 2019 and 2020. We used an Indigenist research approach, community-based Participatory Action Research framework and ‘yarning’ to understand whether Community Panels were an acceptable and appropriate way of engaging First Nations Peoples. Forty First Nations participants were purposively recruited through local and cultural networks. Panels heard evidence supporting various pandemic response strategies, and cross-questioned public health experts.Results All 40 participants from the 5 panels verbally indicated strong support of the Community Panels approach as an effective way of engaging First Nations Peoples in making decisions about pandemic planning and response strategies. The main theme of ‘respect’ centred on the overarching principle that First Nations Peoples are important in the context of continuation of culture and ongoing political resistance.Conclusion First Nations Community Panels are a way of enabling active participation of First Nations peoples, increasing knowledge and understanding, and a way for government and policymakers to respectfully listen to First Nations opinions and ...